2018
DOI: 10.3928/01477447-20180409-01
|View full text |Cite
|
Sign up to set email alerts
|

Relative Complications and Trends of Outpatient Total Shoulder Arthroplasty

Abstract: Outpatient arthroplasty is an appealing option among select patient populations as a mechanism for reducing health care expenditure. The purpose of this study was to determine the nationwide trends and complication profile of outpatient total shoulder arthroplasty (TSA). The authors reviewed a national administrative claims database to identify patients undergoing TSA as outpatients and inpatients from 2007 to 2016. The incidence of perioperative surgical and medical complications was determined by querying fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
66
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(67 citation statements)
references
References 33 publications
0
66
0
1
Order By: Relevance
“…Following full text review, 26 articles were included in the review (Figure 1). Of the included studies, 18 articles discussed complications, readmissions, and safety, [16][17][18][19]21,22,[24][25][26][27][28][29][30][31][32][33]40,41 7 articles discussed patient selection, 21,[27][28][29][30][31]40 6 articles discussed pain management, 20,28,[34][35][36][37] 6 articles discussed the cost implications of outpatient surgery, 15,22,23,30,38,41 2 articles discussed patient satisfaction, 24,32 and 1 article discussed surgeon satisfaction. 15 The level of evidence of the included articles ranges from Level II to Level V.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following full text review, 26 articles were included in the review (Figure 1). Of the included studies, 18 articles discussed complications, readmissions, and safety, [16][17][18][19]21,22,[24][25][26][27][28][29][30][31][32][33]40,41 7 articles discussed patient selection, 21,[27][28][29][30][31]40 6 articles discussed pain management, 20,28,[34][35][36][37] 6 articles discussed the cost implications of outpatient surgery, 15,22,23,30,38,41 2 articles discussed patient satisfaction, 24,32 and 1 article discussed surgeon satisfaction. 15 The level of evidence of the included articles ranges from Level II to Level V.…”
Section: Resultsmentioning
confidence: 99%
“…16,17,24,32,40 Brolin et al found no statistical difference between inpatient (10%) and outpatient (13%) complication rates when comparing 30 inpatient and outpatient SA performed by a single surgeon, 29 and Arshi et al found higher rates of surgical site infections (SSI) requiring irrigation and debridement at 6 months (OR ¼ 1.49; 95% confidence interval (CI), 1.01-2.19; P ¼ .045) and 1 year (OR ¼ 1.65; 95% CI, 1.15-2.35; P < .001) in an outpatient SA cohort. 26 Medical complications were more common in inpatient cohorts relative to outpatient SA patients, with complications ranging from 0%-17.7% for inpatients and 0%-15.9% for outpatients. 16,18,21,22,24,25,28,30,31 Common complications identified in the inpatient vs outpatient cohorts were blood transfusion (range, 4.48-4.7% vs 0.49-3.5%), urinary tract infection (range 0.9-8.7% vs 0.58-6.8%) and acute kidney injury (range, 0.4-4.3% vs 0-4.5%).…”
Section: Complications Readmissions and Safetymentioning
confidence: 93%
See 1 more Smart Citation
“…The revision rates were reported in three studies, with a revision incidence of 1.9% (N = 50) in the outpatient group and 1.6% (N = 346) in the inpatient group. At 12 month follow-up, Cancienne et al [8] and Arshi et al [29] found no statistically significant difference in TSA revision at 12 months. Similarly, Erickson et al [18] reported no difference in revision between both groups at 24 months.…”
Section: Complications and Revisionsmentioning
confidence: 93%
“…Additionally, Cancienne et al [8] found that outpatient TSA had significantly less urinary tract infections (P = 0.003) and less blood transfusions (P = 0.028) [8]. On the other hand, Arshi et al [29] found that outpatient TSA was associated with higher rates of surgical site infections.…”
Section: Complications and Revisionsmentioning
confidence: 99%